Comparison of dexmedetomidine-propofol and ketamine-propofol administration during sedation-guided upper gastrointestinal system endoscopy - Tekeli, Arzu Esen (Medicine (Baltimore), 2020)
BACKGROUND: Dexmedetomidine and ketamine popular sedative agents that result in minimal respiratory depression and the presence of analgesic activity. We aimed to compare the effectiveness and safety of a dexmedetomidine-propofol combination and a ketamine-propofol combination during upper gastrointestinal system endoscopy. METHODS: The study commenced after receiving approval from the local ethics committee. Patients between 18 and 60 years in the American Society of Anesthesiologists (ASA) I and II groups were included. Patients who had severe organ disease, who had allergies to the study drugs, and who refused to participate were excluded. Cases were randomized into a dexmedetomidine-propofol group (Group D, n = 30) and a ketamine-propofol group (Group K, n = 30). Cardiac monitoring, peripheral oxygen saturation, and bispectral index (BIS) monitoring were performed. Group D received 1 mg/kg dexmedetomidine + 0.5 mg/kg propofol intravenous (IV) bolus, 0.5 μg/kg/h dexmedetomidine + 0.5 mg/kg/h propfol infusion. Group K received 1 mg/kg ketamine + 0.125 mL/kg propofol iv bolus, 0.25 mg/kg/h ketamine + 0.125 mL/kg/h propfol infusion. Patients were followed up with a Ramsay Sedation Scale (RSS) of ≥4. Means, standard deviations, lowest and highest frequency values, and ratio values were used for descriptive statistics, and the SPSS 22.0 program was used for statistical analyses. RESULTS: In Group K, recovery time and mean blood pressure (MBP) values were significantly shorter. Furthermore, coughing rate, pulse, and BIS values were higher than in Group D (P < .05). Although there were no significant differences between the groups in terms of endoscopic tolerance and endoscopist satisfaction, we observed that the dexmedetomidine group experienced more comfortable levels of sedation. CONCLUSION: Dexmedetomidine-propofol and ketamine-propofol combinations may be suitable and safe for endoscopy sedation due to their different properties. It was observed that the dexmedetomidine-propfol combination was superior in terms of sedation depth and that the ketamine-propofol combination was superior in terms of early recovery. As a result, we suggest the dexmedetomidine-propofol combination for upper gastrointestinal system endoscopy sedation due to hemodynamic stability and minimal adverse effects.